Retrospective analysis of complications after surgical treatment of congenital kyphosis in children - Mezentsev, Andrey; Demchenko, Dmytro; Petrenko, Dmytro (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Congenital kyphosis occurs as a result of a disruption in the formation or vertebral segmentation in the presence of active semi-vertebra, characterized by rapid progression and, as a rule, development of significant neurological complications. The main surgeries at congenital kyphosis are: ventral and/or posterior fusion in situ, with or without metal devices, vertebroectomy and osteotomy in different modifications. Among postoperative complications in patients with congenital kyphosis, the most common are neurological and fractures of metal devices. Objective: to conduct a retrospective analysis of surgical outcomes of the treatment of congenital kyphosis in children. Methods: case histories were analyzed, patients with congenital kyphosis, whose age did not exceed 18 years, and the follow-up period was at least 2 years after the operation. We assessed the value of the total and local kyphosis, lumbar lordosis. Infectious complications, deformity progression, as well as the complications associated with the instability of metal devices were analyzed. Results: of the 25 patients, 5 had complications: metal device instability with the loss of correction in 3 cases, the infectious — 1, the increase in total kyphosis — 1. In 4 patients revision surgeries were made. Conclusions: use of existing technologies for surgical treatment of congenital kyphosis leads to development of complications after operations. Their main reasons were tactical errors associated with inadequate evaluation of growth potential of the spine, as well as instability of metal devices due to lack of mature bone block. It is necessary to create a technology that can model the growth of the spine and contribute the bone block in the place of osteotomy.